2018
DOI: 10.12688/f1000research.15604.1
|View full text |Cite
|
Sign up to set email alerts
|

Androgen-dependent alternative mRNA isoform expression in prostate cancer cells

Abstract: Background: Androgen steroid hormones are key drivers of prostate cancer. Previous work has shown that androgens can drive the expression of alternative mRNA isoforms as well as transcriptional changes in prostate cancer cells. Yet to what extent androgens control alternative mRNA isoforms and how these are expressed and differentially regulated in prostate tumours is unknown. Methods: Here we have used RNA-Seq data to globally identify alternative mRNA isoform expression under androgen control in prostate can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 121 publications
(66 reference statements)
0
19
2
Order By: Relevance
“…The data presented here imply that androgens also have an important role in controlling splicing patterns, particularly those that relate to epithelial functions. Previous studies identified just a small number of alternative exons that are controlled by androgens in prostate cancer cells, none of which overlapped with the current study (9,11). We suggest that an important reason for this discrepancy is because previously splicing patterns were monitored after 24 hours of androgen exposure.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…The data presented here imply that androgens also have an important role in controlling splicing patterns, particularly those that relate to epithelial functions. Previous studies identified just a small number of alternative exons that are controlled by androgens in prostate cancer cells, none of which overlapped with the current study (9,11). We suggest that an important reason for this discrepancy is because previously splicing patterns were monitored after 24 hours of androgen exposure.…”
Section: Discussioncontrasting
confidence: 86%
“…The roles of both androgens and the AR in transcription have been intensively investigated. However, androgens and the AR also regulate alternative pre-mRNA splicing through still largely unknown mechanisms (6)(7)(8)(9)(10)(11). This represents a very important knowledge gap: alternative splicing patterns in cancer cells can generate protein isoforms with different biological functions (12), and is a key process in the generation of biological heterogeneity in prostate cancer (13,14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 18 , 19 APPBP2, TRIM37 54 , 55 GPS1 GPS1, ANAPC11, DUS1L, RFNG, OXLD1, MRPL12, LRRC45, CENPX, ASPSCR1, CCDC137, FAAP100, CEP131, MCRIP1, DCXR, PCYT2, SIRT7 17q25.3 Ref. 19 DUS1L 56 POLR2I POLR2I, TIMM50, MRPS12, RBM42, C19orf47, NFKBIB, TBCB, SDHAF1, YIF1B, EXOSC5 19q13.12 Neither Pancreatic cancer 57 and bladder cancer 58 YIF1B 59 ZNF420 ZNF420, ZNF461, ZNF567, ZNF383, ZNF566, ZFP30, ZNF260, ZNF585A, ZNF570, ZNF527, ZNF571, ZNF569, ZFP14, ZNF568 19q13.12 Neither Pancreatic cancer 57 and bladder cancer 58 ZFP14 60 HSPBP1 HSPBP1, ZNF865, ZNF579, ZNF787, EPN1, FIZ1, ZNF444, ZNF524, ZNF580, ZNF784, RPL28, ZNF581 19q13.42 Refs. 18 , 19 RPL28 61 ZNF134 ZNF134, ZNF304, ZNF551, ZNF776, ZNF17 19q13.43 Refs.…”
Section: Resultsmentioning
confidence: 99%
“…Disruptions of the androgen system have been linked to the development of hormone-dependent prostate cancer, systemic autoimmune disorders, diabetes mellitus, infertility, and other health issues [187,[191][192][193][194][195]. DHEA-deficiency or excess could impact its role in regulating adipokine expression and secretion [196].…”
Section: Steroid Hormonesmentioning
confidence: 99%